Usaha Durian di Desa Barung-barung Balantai Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan Tahun 2012 - 2024 - Salsabila, Ahada; Najmi, Najmi (Jurnal Kronologi, 2025)
Durian (Durio zibethinus Murr.) is an exotic tropical fruit plant with a distinctive taste and aroma. This fruit is known as the "king of fruits" and is loved by various levels of society because of its uniqueness. This study aims to analyze the background of Mr. Zulfikal's durian business in Barung - Barung Balantai village, Koto XI Tarusan District, Pesisir Selatan Regency in 2012 - 2024, as well as the development of Mr. Zulfikal's durian business. This study uses a historical method with heuristic stages, source criticism, interpretation, and historiography. Data were collected through literature studies, observations, and direct interviews with durian business owners. The results show that Mr. Zulfikal began his life journey as a street vendor because that was the only source of income to meet his family's needs. Over time, each durian season brought an increase in income that continued to grow every year, Zulfikal's durian business grew rapidly, from a street vendor to a large-scale durian processing entrepreneur with peeled durian products (dulpas) marketed outside West Sumatra. From a socio-economic perspective, this business has created jobs for the local community and increased the income of the owners and workers. The conclusion of this study is that Mr. Zulfikal's durian business has experienced rapid growth, going from a small-scale vendor to a large-scale durian enterprise. This business not only increases revenue but also creates jobs and positively contributes to the local economy.